"Gayl Jones and Travel No-Where" - Kelley, Wyn (Review of International American Studies, 2024)
Gayl Jones (USA, b. 1949) writes of journeys throughout the Americas, while also, if implicitly, exploring a global African diaspora. Her epic historical novel Palmares (2021) focuses on Brazil, retelling the story of Zumbi, 17th-century Afro-Brazilian leader of a quilombo, or fortified rebel city. Palmares did finally fall to Portuguese colonial militias in 1694-5, and in her book Gayl Jones’s protagonist, Almeyda, then travels to what she hopes will be a new or second Palmares. Her journey, however, frustratingly and paradoxically seems to get her nowhere. But, as we will see, this nowhere reveals the No-Where of Palmarians’ lives, a placelessness that seems uncertain, but at the same time offers freedom, or at least imaginative space. Like legendary “flying Africans,” people who escaped enslavement by leaping into the air, Jones’s characters appear to launch themselves into an unknown, a Not-Know-Where that may take them to Africa or somewhere utterly unanticipated. We can find other versions of this ambiguous travel in Gayl Jones’s drama, The Ancestor: A Street Play (1975; 2020), and her novel, The Birdcatcher (1986; 2022)—and even in the works of Toni Morrison, whose novels show similar concern with what Saidiya Hartman calls “critical fabulation”: attempts to rethink history outside archives and beyond maps.